Implementation of Guidance and Counseling in Kaliwungu Elementary School - Ngaenu Rofiqoh; Lutfia Islahati; Nita Eka Rahmawati; Moh Salimi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Guidance and counseling is an inseparable part of the education system. Likewise at Kaliwungu Elementary School which has implemented the Guidance and Counseling program. The Guidance and Counseling Program is implemented to direct and overcome problems experienced by students, both in academic and non-academic fields. These problems include lazy and slow in learning, undisciplined, fight, and so forth. The purpose of this study was to find out how the implementation of guidance and counseling programs at  Kaliwungu elementary school. This method of research is a qualitative descriptive study with interview and observation technique. The results of this study indicate that the implementation of the guidance and counseling program at Kaliwungu elementary school is carried out by the class teacher. The form of guidance given is individual guidance and group guidance. Individual counseling is an ecletive counseling by the teacher advising and directing students according to the problem. Group guidance in the form of remedial teaching and home room program